Management of hydrocephalus in a pediatric bifocal germinoma - Ricardo Santos de Oliveira; Rodrigo Inácio Pongeluppi; Elvis Terci Valera (Brazilian Society for Pediatric Neurosurgery, 2020)
Germinomas represent the most frequent tumour type in the pineal region. However, the synchronous involvement of the suprasellar region, frequently termed bifocal intracranial germinoma (BFG) is quite rare. A literature search identified a further of 48 pediatric cases with a median age of 12.9 years. BFG is known to be highly radiosensitive. We presented a clinical case of pediatric bifocal germinoma. A 14-year-old boy presented with clinical features of progressive headaches since three months associated with vomits. MR showed two distinct lesions in the pineal and suprasellar regions. Neuroaxis spine MR was normal. Tumor markers for germ cell tumors from blood and cerebrospinal fluid were within the normal range. An endoscopic procedure was performed to treat the hydrocephalus (endoscopic third ventriculostomy) and, in the same procedure the suprasellar lesion was biopsied and the histology revealed a germinoma. She received chemotherapy and a focal radiotherapy covering the sites of primary disease and the ventricular system. Three months after the completion of treatment, the patient achieved a complete clinical and radiological response, which was maintained during the 5-years follow-up period. The optimum management of primary intracranial pineal and suprasellar (bifocal) germinomas still remains controversial. The definition as either localized or disseminated disease has major implications on required treatment and its associated late morbidity. Prospective studies with large cooperative groups worldwide and consensus meetings may reduce uncertainties regarding available management options.